(untitled) (International Conference on Computers in Education, 2016)
In recent years, Computer programming has become a very important subject, and it is a basic literacy in the digital age. But learning programming skills is not an easy task as supported by many studies. On the other hand, many studies have concluded that student question generation has a positive effect on students’ learning. However, few studies have geared toward supporting its use in programming classes. Therefore, this Study aimed to develop a programming learning system named Peer-Interaction Programming Learning System based on a question generation strategy. The system was built by adding and intergrading learning assistance functions by system initiative into existing open-source Q&A system. In this paper, we reported the design of the system and its user interface, identified several related systems, discussed our motivation and underlying teaching philosophy.